FRI0227 Risk factors for skin reactions to allopurinol in the kinh population of vietnam. (12th June 2018) - Bardin, T.; Le, L.G.; Buy, T.M.K.; Do, A.D.; Le, H.; Do, M.D.; Hoang, V.A.; Le, A.N.; Nguyen, Q.D.; Le, N.H.; Richette, P.; Resche-Rigon, M.; et al.
Abstract : Background: Allopurinol (ALLO) exposes to mild (M) and severe (S) cutaneous adverse reactions (CARs). SCARS have been associated with HLA*B58 01 with various strength of across ethnicities. Little is known about ALLO tolerance in Vietnam (VN). Objectives: The aim of this ongoing prospective study was to investigate risk factors, including HLA*B-58 01, for MCARs and SCARs in the predominant Kinh ethnicity of VN Methods: All included patients were Kinh Vietnamese. SCARs were recruited at Ho Chi Minh City hospitals, MCARs from the same departments and from the Vien Gut clinic at HCMC (specialised in gout care), and tolerant gouty patients (no skin reaction after at least 3 months from the last increment in ALLO dose) at the Vien Gut clinic. Clinical data were prospectively collected and HLA*B-58 01 typing used the PG5801 DNA detection kit (Pharmigene-Taiwan). Fisher exact test for categorical variables and Kruskal/Wilkonson test for quantitative variables were used for statistics. Results: 10 patients experienced a non-fatal SCAR. Toxic necrotic epidermolysis, Stevens-Johnson syndrome and mixed syndrome were diagnosed in 1, 8 and 1 patients respectively. 54 patients stopped ALLO because of MCAR.112 ALLO tolerant patients were recruited. Table 1 shows the main features of interest in the 3 groups. The Odds ratio of HLA*B-58 01 positive patients to develop SCARs was calculated at 171.2 (95% CI: 20; 7889) Conclusions: HLA*B-58 01 was significantly associated with SCARs to ALLO in the VN Kinh population. Other known factors but not high ALLO dose were also associated. The only association with MCARs was lack of ALLO titration. Acknowledgements: ART Viggo Disclosure of Interest: None declared